Nonmydriatic Retinal Photography in the Outpatient Neurology Resident Clinic. Issue 1 (March 2022) - Pyatka, Nataliya; Banks, Matthew K.; Fotedar, Neel; DeLozier, Sarah J.; Morgan, Michael; Preston, David C.
Abstract : Background: The funduscopic examination is an essential component of the neurologic examination. However, examination of the ocular fundus with a direct ophthalmoscope is often difficult. Nonmydriatic ocular fundus photography allows direct visualization of the ocular fundus with high-quality photographs. We used nonmydriatic ocular fundus photography to improve patient care and funduscopy skills of residents in the Neurology Resident Clinic. Methods: At the time of triage, funduscopic photographs of all new neurology resident clinic patients were taken. The images were imported into the hospital's imaging software. The residents completed a full neurologic examination, including a funduscopic examination with a handheld ophthalmoscope. At the time of staffing the patients with the attendings, the residents received immediate feedback and teaching on retina photograph evaluation. Results: A total of 255 patients were enrolled. Of those, 230 (90%) had at least one high-quality funduscopic photograph. Retinal photographs were normal in 161 (70%). Out of the 69 abnormal photographs, only 7% of abnormalities were detected by the residents. Ninety-three percent of residents found the retinal photographs useful. Conclusions: Nonmydriatic ocular fundus photography improved the care in patients presenting to a Neurology resident clinic and facilitated residents in recognizing funduscopic findings. Its benefits are clear when one considers (1) the high risk of negative patient outcomes and possible medicolegal consequences due to missed findings, (2) the ease of incorporating retinal photographs into the patients' medical records, and (3) the benefit of improving resident education in regard to the ophthalmologic examination.